Hi, just like to check my answer with someone for the this question calculate y"+9y=H(t-1) y(0)=0 y'(0)=-2 using laplace method H is heaviside fuction my solution: y=cos(3t)-2sin(3t)/3 + H(t-1)/9(H(t-1) + cos (3t-3) ) thanks
Follow Math Help Forum on Facebook and Google+
Originally Posted by Fibonacci Hi, just like to check my answer with someone for the this question calculate y"+9y=H(t-1) y(0)=0 y'(0)=-2 using laplace method H is heaviside fuction my solution: y=cos(3t)-2sin(3t)/3 + H(t-1)/9(H(t-1) + cos (3t-3) ) thanks You can substitute your solution into the DE to check if it works or not.
View Tag Cloud